JAPANEDU Volume 4 Issue 2, December 2019 FULLTEXT - JAPANEDU, Editor in Chief (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2019)
JAPANEDU FULLTEXT Vol. 4 Issue 2 December 2019 including Front Cover, Table of Contents, and Back Cover